2011
DOI: 10.1111/j.1748-1716.2011.02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute normobaric hyperoxia transiently attenuates plasma erythropoietin concentration in healthy males: evidence against the ‘normobaric oxygen paradox’ theory

Abstract: In contrast to the 'normobaric oxygen paradox' theory, the present results indicate that a short period of normobaric O(2) breathing does not increase the EPO concentration in aerobically fit healthy males. Increased O(2) tension suppresses the EPO concentration 3 and 5 h after the exposure; thereafter EPO seems to change in a manner consistent with natural diurnal variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 42 publications
5
18
0
Order By: Relevance
“…Compared to the placebo, the IHH protocol induced a transient reduction in [EPO] within the initial 8 h following the IHH protocol. Our results thus present further evidence against the existence of NOP and concur with the findings of Keramidas et al (2011), McGuire et al (2006, and Momeni et al (2011).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Compared to the placebo, the IHH protocol induced a transient reduction in [EPO] within the initial 8 h following the IHH protocol. Our results thus present further evidence against the existence of NOP and concur with the findings of Keramidas et al (2011), McGuire et al (2006, and Momeni et al (2011).…”
Section: Discussionsupporting
confidence: 95%
“…In particular, subsequent studies either did not find augmented EPO production following an acute normobaric hyperoxic exposure (McGuire et al 2006;Momeni et al 2011) or have even shown a suppressive effect on EPO production (Keramidas et al 2011). This is in line with the results of previous studies showing the suppression of erythropoietic activity following normobaric hyperoxia in humans (Kokot et al 1994a, b).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…We instead analyzed the variation of serum EPO expressed as percent of baseline value to exclude any individual circadian EPO variations. Recently, Keramidas et al (2011) did not Wnd any diVerence between EPO levels after 2 h administration of oxygen or air in a single blinded counterbalanced crossover study protocol. They only found, like Balestra and our group, that 100% oxygen was followed by a transient decrease in EPO level, after a period between 3 and 8 h.…”
Section: Discussionmentioning
confidence: 98%
“…Keramidas et al. () observed diurnal variation of a nadir in values of EPO in the morning hours and zenith levels during the evening and night hours. Additional hematological measurements prior to the experimental period would provide a more accurate baseline interpretation.…”
Section: Discussionmentioning
confidence: 99%